2012
DOI: 10.1007/s10198-012-0390-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of time cost of physical exercise on health outcomes by older adults: the DR’s EXTRA Study

Abstract: When the motivation for exercise is high and people are retired, the cost of time used for physical exercise may be lower and individuals may exercise more compared to individuals with a low motivational level and in working life. The aim was to study the effect of time cost of physical exercise on the amount of physical exercise and on health-related quality of life. We used 2-year data (n = 1,292) from a 4-year randomised controlled trial in a population-based sample of Eastern Finnish men and women, 57-78 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…This is in line with an earlier study of the value of travel time, which found that the value was 22.5% lower among the unemployed [21]. The present study, like an earlier study [22], suggests that the opportunity cost (value of leisure activity forgone) may be lower for unemployed individuals. For unemployed individuals in particular, then, it should be more relevant to base the yardstick on WTP for cleaning or similar.…”
Section: Strengths and Weaknesses Of The Studysupporting
confidence: 92%
“…This is in line with an earlier study of the value of travel time, which found that the value was 22.5% lower among the unemployed [21]. The present study, like an earlier study [22], suggests that the opportunity cost (value of leisure activity forgone) may be lower for unemployed individuals. For unemployed individuals in particular, then, it should be more relevant to base the yardstick on WTP for cleaning or similar.…”
Section: Strengths and Weaknesses Of The Studysupporting
confidence: 92%
“…Among the included studies, 36 examined the effects of retirement on PA ( Supplementary Table S2d ). The absence of work activities provides an opportunity for free time; thus, it is not surprising to see that many studies showed an increase in leisure-time PA after retirement ( Brown, Heesch, & Miller, 2009 ; Eibich, 2015 ; Henkens, van Solinge, & Gallo, 2008 ; Holstila, Manty, Rahkonen, Lahelma, & Lahti, 2017 ; Insler, 2014 ; Koeneman et al, 2012 ; Kuvaja-Köllner, Valtonen, Komulainen, Hassinen, & Rauramaa, 2013 ; Lahti & Laaksonen, 2011 ; Midanik, Soghikian, Ransom, & Tekawa, 1995 ; Motegi, Nishimura, & Terada, 2016 ; Oshio & Kan, 2017 ; Sjösten et al, 2012 ; Stenholm et al, 2016 ; Syse et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…To address the endogeneity problem and the potential reverse causality, this study employs the method of Instrumental Variable (IV) estimation which has been well proven in the literature for using the data as similar to the data this paper dealing with. Previous studies (Dave, et al, 2008;Latif, 2012;Kuvaja-Kӧllner, et al, 2013;Eibich, 2015;Zhu, 2016;Godard, 2016;Hessel, 2016;Motegi, et al, 2016) suggested that the estimation would be restricted to that retirement was the only channel through which individual health outcomes could be affected by the instrumental variables. A good instrument should be strongly correlated with actual retirement behavior, but it should not directly affect health outcomes.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…To evaluate whether the effects of retirement on health differ by marital status, the goal of this paper is to identify the differences in the effects of retirement on physical/mental health as health-related quality of life (HRQOL) across marital status subgroups (married, divorced, never married, and widowed) for the retirement-aged adults (55-74 years of age) for all 50 states and Washington D.C. from 2005 to 2016 in the U.S. The retirement ages as 55-74 years of age is defined by the study (Kuvaja-Kӧllner, et al, 2013), but the retirement ages have been widely defined from 45 to 79 years of age in the earlier studies (Bonsang, et al, 2012;Eibich, 2015;Vo, et al, 2015;Hessel, 2016;Zhu, 2016). The period from 2005 to 2016 is meaningful for the social security retirement benefitsboth the early retirement age of 62 and the full retirement age of 66 had remained unchanged only during the period in the U.S.…”
Section: Introductionmentioning
confidence: 99%